Establishment and application of national reference panels for SARS-CoV-2 antigen detection kit - Tingting Ma; Donglai Liu; Keliang Lyu; Tingting Gao; Dawei Shi; Lanqing Zhao; Shu Shen; Yabin Tian; Sihong Xu; Haiwei Zhou (Elsevier, 2023)
To develop a national reference panel for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antigen detection kit and establish a quality standard. The cultures of SARS-CoV-2 and other pathogens were collected to establish a national reference panel for SARS-CoV-2 antigen detection. The stability and homogeneity of the reference panel were evaluated. Based on World Health Organization (WHO) guidance and nucleic acid quantitative results, a quality standard reference panel was established. Currently, three generations of SARS-CoV-2 antigen national reference materials with batch numbers 370095-202001, 370095-202202, and 370095-202203 have been successfully established. These national reference panels comprised 8 positive samples, 20 negative samples, 1 repetitive sample, and 1 lower detection limit sample. The stability and homogeneity of the reference panel meet the requirements. The quality standards are as follows: the positive and negative coincidence rates are 8/8 and 20/20, respectively. The 10 test results of the medium and low-concentration repetitive reference materials should be positive, and the color rendering should be uniform (or the coefficient of variance should not be higher than 20.0%). The lower detection limit should be at least 5 × 105 U/mL (equivalent to copies/mL), and higher concentrations above the lower detection limit must be positive. A national reference panel for the SARS-CoV-2 antigen detection kit has been established. As the standard of SARS-CoV-2 antigen reagents, the reference panel has played a crucial role in the pre-marketing quality evaluation and post-marketing quality supervision in China.